Aluminum to germanium inversion in mullite‐type RAlGeO5: Characterization of a rare phenomenon for R = Y, Sm–Lu. Issue 1 (8th September 2021) - Ghosh, Kowsik; Murshed, M. Mangir; Fischer, Michael; Gesing, Thorsten M.
Abstract: Mullite‐type R Mn2 O5 ( R  = Y, rare‐earth element) ceramics are of ongoing research attentions because of their interesting crystal‐chemical, physical, and thermal properties. We report a detailed structural, spectroscopic and thermal analysis of the series of mullite‐type R AlGeO5 ( R  = Y, Sm‐Lu) phases. Polycrystalline samples are prepared by solid‐state synthesis methods. Each sample is characterized by X‐ray powder diffraction followed by Rietveld refinements, showing that they are isotypic and crystallize in the space group Pbam . The change of the metric parameters is explained in term of the lanthanide contraction effect. A rare inversion of Al/Ge between octahedral and pyramidal sites have been observed for these mullite‐type so called O10 compounds, and the inversion parameter found to be between 0.22(1) and 0.30(1) for different R ‐cations. The bond distances and their bond valence sums (BVSs) support the respective inversions. Density functional theory (DFT) calculated phonon density of states (PDOS) and electronic band structures are compared for the vibrational and electronic band gap features respectively. Analysis of UV/Vis absorption spectra using both derivation of absorption spectra fitting (DASF) and Tauc's methods demonstrates that each of the R AlGeO5 O10 compounds is high bandgap semiconductor, possessing direct transition between 4.1(1) and 5.4(1) eV. Both Raman and Fourier transform infrared spectra show clear red shift (quasi‐harmonic) of the vibrational wavenumbers with respect to the ionic radii of the R ‐cations. Selective Raman bands at higher wavenumber region further complement the inversion of Al/Ge between two coordination sites. The higher decomposition temperature of the R AlGeO5 compounds, compared to those of R Mn2 O5 phases, is explained in terms of higher bond strength of Al/Ge‐O than those of Mn‐O. Irrespective to the inversion between Al‐ and Ge‐sites, the decomposition temperature also depends on the type of R ‐cation in R AlGeO5 . Abstract : Rare inversion of Al/Ge between octahedral and pyramidal sites are observed in mullite‐type RAlGeO5 (R = Y, Eu‐Lu) ceramics. The bond distances and their bond valence sums and selective vibrational bands support the inversions. UV/Vis absorption spectra analyzed by both DASF and Tauc's methods demonstrate the direct transition and complemented by DFT calculations.